Nipah virus survey in Pteropus medius of eastern and northeastern region of India, 2022–2023 - Mohandas, Sreelekshmy; Patil, Dilip; Mathapati, Basavaraj; Rai, Vishal; Shete, Anita; Belani, Sujeet; Kumar, Abhinendra; Sahay, Rima; Patil, Deepak; Yadav, Pragya D. (Frontiers in Microbiology, 2024)
IntroductionIndia has experienced seven outbreaks of the Nipah virus (NiV) since 2001, primarily occurring in the southern and eastern regions of the country. The southern region has been the main site for these outbreaks. In contrast, the eastern region, which borders Bangladesh, has not reported any outbreaks since 2007. However, Bangladesh continues to experience nearly annual outbreaks, indicating a significant lack of surveillance in that area. To improve the country’s preparedness and to gather support for enhancing public health surveillance in eastern and northeastern states near the area affected by the NiV, a cross-sectional survey was conducted to determine the prevalence of NiV in the bat species Pteropus medius in Bihar, West Bengal, Assam, and Meghalaya states in India, which are adjacent to Bangladesh.MethodsThroat and rectal swabs, blood samples, and organ samples were collected. Real-time quantitative reverse transcription PCR (qRT-PCR) was utilized for the detection of Nipah viral RNA, and sequencing was conducted for further confirmation. Bat IgG enzyme-linked immunosorbent assay (ELISA) was employed for antibody detection.ResultsThroat and rectal swab samples of 212 P. medius tested for NiV using qRT- PCR were found negative, whereas organ samples of two (one each from West Bengal and Bihar) out of the 10 bats collected tested positive. The retrieved NiV genome (~91%) showed close homology to the NiV-Bangladesh genotype indicating the circulation of two geographically distinct NiV strains in India. The seroprevalence estimated by ELISA ranged from 23 to 65% in the studied states.DiscussionThe serological and virological evidence obtained from the study indicates that a broader geographical area is under threat of spillover in India. It’s crucial to implement a One Health approach connecting bat surveillance studies with human surveillance and risk factor studies in the region.